Construction planning and scheduling - Hinze, Jimmie (Upper Saddle River, N.J. : Pearson Prentice Hall, 2012)
Construction Planning and Scheduling, Fourth Edition offers broad coverage of all major scheduling subjects. This comprehensive resource is designed for construction management, planning and scheduling. It follows a logical progression, introducing precedence diagramming early and following with chapters on activity durations, resource allocations, network schedules, and more. It reflects current trends in scheduling (short-interval scheduling, computer scheduling, linear scheduling etc.) and includes chapters on arrow diagramming and PERT. With an eye on application, it includes a unique discussion of contract provisions related to scheduling and incorporates a sample project throughout.
1. Introduction 2. Developing a Network Model 3. Precedence Diagrams 4. Determining Activity Durations 5. Time in Contract Provisions 6. Resource Allocation and Resource Leveling 7. Money and Network Schedules 8. Project Monitoring and Control 9. Computer Scheduling 10. Earned Value: A Means for Integrating Costs and Schedule 11. The Impact of Scheduling Decisions on Productivity 12. CPM In Dispute Resolution and Litigation 13. Short-Interval Schedules 14. Linear Scheduling 15. PERT: Program Evaluation and Review Technique 16. Arrow Diagrams REFERENCES ADDITIONAL REFERENCES INDEX
engineering bookfair2015
Includes bibliographical references and index.
Keywords: Building -- Superintendence; Production scheduling